A haemochromatosis-causing HFE mutation is associated with SARS-CoV-2 susceptibility in the Czech population - Hubacek, J A; Philipp, T; Adamkova, V; Majek, O; Dusek, L (Clinica chimica acta; international journal of clinical chemistry, 2023)
BACKGROUND: Coronavirus disease (COVID-19), which is caused by the SARS-CoV-2 virus, has become a global pandemic. While susceptibility to COVID-19 is subject to several external factors, including hypertension, BMI, and the presence of diabetes, it is also genetically determined to a significant extent. Infectious agents require iron (Fe) for proper functioning. Carriers of mutations resulting in increased iron concentrations are understood to be at increased risk of COVID-19. METHODS: We examined HFE genotypes associated with hereditary haemochromatosis (rs1800562 and rs1799945 SNPs) in 617 COVID-19 patients (166 asymptomatic, 246 symptomatic and 205 hospitalised survivors) and 2 559 population-based controls. RESULTS: We found a higher frequency of the minor allele (Tyr282) of the rs1800562 polymorphism (P < 0.002) in patients compared to controls (8.5 % vs 5.5 %). Non-carriers of the minor allele were protected against SARS-Cov-2 infection (OR, 95 %CI; 0.59, 0.42-0.82). The frequency of minor allele carriers was almost identical across asymptomatic, symptomatic, and hospitalised survivors. The rs1799945 variant did not affect disease severity and its occurrence was almost identical in patients and controls (P between 0.58 and 0.84). CONCLUSIONS: In conclusion, our results indicate that presence of the rs1800562 minor allele, which is associated with hereditary haemochromatosis (thus increased levels of plasma Fe), increases susceptibility to SARS-CoV-2.
Keywords: Polymorphism; Susceptibility; Hemochromatosis; mutace; železo; Česká republika; protein hemochromatózy; hemochromatóza; Histocompatibility Antigens Class I; MHC antigeny I. třídy; jednonukleotidový polymorfismus; SARS-CoV-2; Czech Republic; Hemochromatosis Protein; Polymorphism, Single Nucleotide; lidé; Iron; Humans; HFE; Mutation; COVID-19